Assessment and management of the first epileptic seizure - Herrera, Manuel (2021)
Epileptic seizures are a common cause of medical consultation in the emergency room and in outpatient settings. The evaluation of the first epileptic seizure is of upmost importance as not all patients presenting with seizures have epilepsy (two or more unprovoked crises separated more than 24 hours; one single crisis with a high risk of recurrence (>60%); or evidence of an epileptic syndrome needing treatment based on the definition by the International League against Epilepsy). On the other hand, not every patient with a first episode should be just observed not offering proper treatment. This decision is based on the risk of recurrence. For that purpose, the American Academy of Neurology (AAN) recommends classifying the first seizures into five groups depending on the risk of recurrence, these groups are: patients with provoked seizures; patients with acute symptomatic seizures; patients with remote symptomatic seizures; first seizure associated with an epileptic syndrome, and first seizure of unknown origin. The AAN guidelines for the management of the first seizure published in 2015 suggests that patients with symptomatic remote seizures (non-evolutive and old cerebral lesions), patients with interictal epileptiform abnormalities, patients with abnormal findings on MRI or CT scan, and patients with nocturnal seizures had a high risk for recurrence (>60%) and should be treated. Current evidence suggests that there is no difference in early or delay treatment for controlling seizures at the long-term.